Change in dynamic postural control after a training program in collegiate soccer players with unilateral chronic ankle instability - Sadakuni, D.; Takeuchi, K.; Tsukuda, F.; Komatsu, T. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Improving dynamic postural stability after lateral ankle sprain due to chronic ankle instability helps prevent recurrence, and changes in dynamic postural stability can be assessed with the Star Excursion Balance Test. To date, no studies have examined the change in Star Excursion Balance Test score after the end of a balance training program or whether chronic ankle instability affects the rate of change. To examine the effect of chronic ankle instability on changes in Star Excursion Balance Test. score over time after a balance training program. METHODS: Fifteen collegiate soccer players with chronic ankle instability selected with the Cumberland Ankle Instability Tool and ultrasonography. Participants completed a 6-week balance training program. We assessed the Star Excursion Balance Test 5 times (before and immediately after the program and 2, 4, and 6 weeks later) and examined differences in the duration of training effects by a 2-way analysis of variance, with Bonferroni correction for post hoc comparisons to explain any significant interactions. The significance level for all analyses was set at P<0.05. We performed statistical analyses with SPSS v. 25. RESULTS: Analysis of the posterolateral and posteromedial scores in Star Excursion Balance Test showed a significant effect of time. Post hoc analysis of the posterolateral score showed that for each leg, participants reached significantly farther after the program than before (P=0.012). The posterolateral scores at 2, 4, and 6 weeks after the training program did not differ from before the program, but the posteromedial score was significantly improved immediately after the program (P=0.008) and also 2 (P=0.004) and 4 weeks later (P=0.006). CONCLUSIONS: A 6-week balance training program to improve dynamic postural control can improve posterolateral and posteromedial scores in people with chronic ankle instability, and the improvements in posteromedial are still present 4 weeks after program completion.